The Modification of Workstation of Lipa Sabbe Weavers as an Effort to Reduce Musculoskeletal Disorders (MSDs) - Muhammad Azrul Syamsul; Helmy Gani; Rizky Maharja; Arni Julian; Andi Tenriola Fittri Kessi; Sitti Fatimah Rahmansyah; Habibi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Work with more loads and equipment design that is not ergonomic results in the use of more energy and riskywork postures. Working in a sitting position basically can reduce stress on the feet, energy consumption,and circulation requirements. Ergonomic workstation is an example of the application of ergonomics whichaims to create a balance between various aspects of each work system and process carried out as an attemptto create a high quality of work and quality of life, as well as an effort to prevent occupational injuries anddiseases. This study aimed at modifying the workstation to reduce MSDs among lipa sabbe weavers. Thisis a quasi-experimental study with one-group pretest-posttest approach to analyze differences in the levelsof MSDs before and after the intervention through modification of ergonomic workstation designs. Theparticipant selection technique used purposive sampling. The research instruments used were Nordic BodyMap questionnaire, camera, and anthropometric measurement tools. Data were analyzed using WilcoxonSigned-Rank Test. The result showed that there is a difference in the level of complaints after modificationof the work media of lipa sabbe weavers. It indicates that modification of work media can reduce MSDsamong lipa sabbe weavers.